Hard carbon material, method for preparing the same, and sodium-ion battery
Patent Information
- Application Number
- CN202510525008.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
使用的溶剂甲苯为有毒物质,产生大量危废
[0017]通过上述技术方案,本公开提供一种硬碳材料及其制备方法和钠离子电池,该方法以煤基沥青与石油基重油为原料,具有原材料廉价、含碳量丰富的特点,其中煤基沥青含有大量的氧杂原子,但缺少烷基侧链;石油基重油则相反,具备一定量的烷基侧链,但缺少氧杂原子。本公开的方法通过共炼技术能够充分利用二者的性质特点,实现煤基沥青和石油基重油的高效转化,并最终制备出结构无序度高、储钠性能好的硬碳材料。将该硬碳材料用于钠离子电池负极时,电池具有较高的首次放电比容量和可逆容量。本公开的方法具有硬碳材料生产率高、设备简单、操作过程容易控制、产品性能稳定的特点,能够有效降低钠离子电池的商业成本,提高市场竞争力。
Smart Images

Figure CN122977347A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of materials, and more specifically, to a hard carbon material, a method for preparing the same, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries, as a potential alternative to lithium-ion batteries, have broad application prospects. However, with lithium prices currently and likely to remain low, cost is a crucial factor for sodium batteries to gain a foothold in the energy storage field. As the anode material for sodium batteries, reducing production costs and improving performance are key to realizing the production and application of sodium-ion batteries.
[0003] The preparation of high-performance hard carbon materials requires raw materials with as low an ash content as possible, a relatively high content of aromatics and a certain amount of alkyl side chains, and a certain amount of oxygen heteroatoms to prevent the formation of ordered structures during high-temperature carbonization. Due to the low carbon yield and high price of hard carbon material precursors, their high cost necessitates the search for raw materials with high carbon yield and low cost. On the other hand, asphalt, as an industrial byproduct, is inexpensive and has a high carbon yield, making it suitable for carbon material preparation. However, asphalt, due to its high aromatic content, easily forms ordered soft carbon materials; therefore, increasing the disorder of carbon materials is key to improving sodium storage performance. How to combine the performance and price advantages of hard carbon materials to obtain anode materials with low cost, high conductivity, disordered structure, and excellent sodium storage performance is a crucial technology that urgently needs development.
[0004] CN117902565A discloses a sodium-ion battery anode material based on resin and pitch, its preparation method, and its application. Pitch and resin are cross-linked, then coked under an inert atmosphere, and finally carbonized at high temperature to obtain a carbon anode material for sodium-ion batteries. The raw material used is resin, which is costly and lacks industrial application value at current lithium battery market prices.
[0005] CN114854444A discloses a method for preparing mesophase pitch from coal / heavy oil hydrorefining residue. The method involves extracting the residue with toluene, and then subjecting the toluene-soluble material to thermal polycondensation in a high-pressure reactor to obtain pre-mesophase pitch with a certain mesophase content. Thermal sedimentation treatment in the high-pressure reactor further homogenizes the composition of the bottom pitch, resulting in a high content of anisotropic components and ultimately yielding mesophase pitch with a mesophase content greater than 95%. The solvent toluene used is a toxic substance, generating a large amount of hazardous waste. The final product is mesophase pitch, which requires further processing to become usable. Summary of the Invention
[0006] The purpose of this disclosure is to provide a hard carbon material, its preparation method, and a sodium-ion battery. This method utilizes a co-refining technique to fully leverage the properties of coal-based pitch and petroleum-based heavy oil, achieving efficient conversion between the two and ultimately producing a hard carbon material with high structural disorder and good sodium storage performance. When this hard carbon material is used as the negative electrode material in a sodium-ion battery, it can effectively improve the battery's electrochemical performance.
[0007] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing hard carbon materials, the method comprising: (1) Coal-based pitch and petroleum-based heavy oil are brought into contact with a modifier to undergo a crosslinking reaction, thereby obtaining crosslinked pitch; (2) The cross-linked asphalt is cured and oxidized to obtain oxidized asphalt; (3) Carbonize the oxidized asphalt.
[0008] Optionally, in step (1), the hydrogen content in the coal-based pitch is 7.0-9.0% by mass, the oxygen content is 4.0% or more by mass, the ash content is less than 0.01% by mass, and the metal content is less than 10 μg / g; the hydrogen content in the petroleum-based heavy oil is 10.0-12.0% by mass, the ash content is less than 0.01% by mass, and the metal content is less than 50 μg / g.
[0009] Optionally, the coal-based pitch includes coal tar pitch and / or direct coal liquefaction pitch, and the petroleum-based heavy oil includes one or more of atmospheric and vacuum residue, catalytic slurry, ethylene tar, styrene tar, and other secondary processing tail oils. The modifier includes inorganic acids and / or organic acids, wherein the inorganic acids include one or more of phosphoric acid, sulfuric acid, carbonic acid and nitric acid, and the organic acids include one or more of sulfonic acid, carboxylic acid and amino acids.
[0010] Optionally, in step (1), the weight ratio of the coal-based pitch, petroleum-based heavy oil and the modifier is 100:(10~50):(5~15). The cross-linking reaction is carried out at a temperature of 150~300℃, a heating rate of 1~10℃ / min, and a holding time of 10~120min.
[0011] Optionally, in step (2), the curing temperature is 250~450℃, the constant temperature time is 1~8h, the heating rate is 1~5℃ / min, and the curing is carried out in an inert gas atmosphere; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen; The oxidation temperature is 250~450℃, the holding time is 1~5h, the heating rate is 1~5℃ / min, and the oxidation is carried out in an oxygen-containing gas atmosphere, which includes air or oxygen.
[0012] Optionally, the curing and oxidation are carried out continuously in a reactor. Preferably, the crosslinked asphalt is placed in the reactor for curing, and after the curing is completed, oxygen-containing gas is introduced into the reactor to carry out the oxidation.
[0013] Optionally, the method further includes, before the curing in step (2), pulverizing the crosslinked asphalt with a pulverizer until the particle size of D10 is <1μm, D50 is <5μm, and D90 is <10μm, to obtain crosslinked asphalt particles, and then curing the crosslinked asphalt particles; the pulverizer includes an air jet mill or a ball mill.
[0014] Optionally, in step (3), the carbonization conditions include: in an inert gas atmosphere, the oxidized asphalt is heated to 1100~1600℃ at a heating rate of 1~10℃ / min for carbonization, and the constant temperature time is 2~8h.
[0015] The second aspect of this disclosure provides a hard carbon material prepared using the method described in the first aspect of this disclosure.
[0016] This disclosure provides a sodium-ion battery in a third aspect, the sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the hard carbon material described in the second aspect of this disclosure.
[0017] Through the above technical solution, this disclosure provides a hard carbon material, its preparation method, and a sodium-ion battery. The method uses coal-based pitch and petroleum-based heavy oil as raw materials, which are characterized by low raw material costs and high carbon content. Coal-based pitch contains a large number of oxygen heteroatoms but lacks alkyl side chains; petroleum-based heavy oil, on the other hand, possesses a certain amount of alkyl side chains but lacks oxygen heteroatoms. The method of this disclosure, through co-refining technology, can fully utilize the properties of both materials to achieve efficient conversion between coal-based pitch and petroleum-based heavy oil, ultimately preparing a hard carbon material with high structural disorder and good sodium storage performance. When this hard carbon material is used as the negative electrode of a sodium-ion battery, the battery exhibits high initial discharge specific capacity and reversible capacity. The method of this disclosure features high hard carbon material production rate, simple equipment, easy-to-control operation process, and stable product performance, effectively reducing the commercial cost of sodium-ion batteries and improving market competitiveness.
[0018] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description
[0019] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a charge-discharge curve of a battery assembled from the hard carbon material prepared in Example 1 of this disclosure at a current density of 0.1C. Figure 2 This is a SEM image of the hard carbon material prepared in Example 1 of this disclosure; Figure 3 This is a TEM image of the hard carbon material prepared in Example 1 of this disclosure. Detailed Implementation
[0020] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.
[0021] The first aspect of this disclosure provides a method for preparing hard carbon materials, the method comprising: (1) Coal-based pitch and petroleum-based heavy oil are brought into contact with a modifier to undergo a crosslinking reaction, thereby obtaining crosslinked pitch; (2) The cross-linked asphalt is cured and oxidized to obtain oxidized asphalt; (3) Carbonize the oxidized asphalt.
[0022] The inventors of this disclosure, through in-depth research, discovered that heteroatoms such as oxygen and nitrogen, along with a suitable amount of alkyl side chains, can weaken the π-π interactions between aromatic hydrocarbons in pitch during crosslinking, preventing the formation of large graphite sheet structures during carbonization, thereby controlling the production of suitable hard carbon materials. The coal-based pitch and petroleum-based heavy oil used in this disclosure contain polycyclic aromatic hydrocarbons and heterocyclic compounds in their molecular structures. Coal-based pitch contains a large amount of heteroatoms such as oxygen and nitrogen, but has a low hydrogen content and an excessively high aromatic carbon ratio, indicating a lack of alkyl side chains. Petroleum-based heavy oil, on the other hand, has a higher hydrogen content than coal-based pitch, indicating the presence of more alkyl side chain structures, but lacks heteroatoms. The inventors of this disclosure aim to use coal-based pitch and petroleum-based heavy oil as raw materials, fully utilizing their properties through co-refining technology to achieve efficient conversion between them, ultimately producing hard carbon materials with high structural disorder and good sodium storage performance. The method of this disclosure features inexpensive raw materials, abundant carbon content, high hard carbon material production rate, simple equipment, easy-to-control operation process, and stable product performance, effectively reducing the commercial cost of sodium-ion batteries and improving market competitiveness.
[0023] In one embodiment of this disclosure, in step (1), the mass content of hydrogen in the coal-based pitch is 7.0~9.0%, the mass content of oxygen is more than 4.0%, the mass content of ash is less than 0.01%, and the metal content is less than 10 μg / g.
[0024] In one embodiment, in step (1), the petroleum-based heavy oil has a hydrogen content of 10.0~12.0%, an ash content of less than 0.01%, and a metal content of less than 50 μg / g.
[0025] In a specific embodiment, before the crosslinking reaction in step (1), coal-based pitch and petroleum-based heavy oil can be pretreated to obtain coal-based pitch and petroleum-based heavy oil with the above parameter range.
[0026] In one embodiment of this disclosure, the coal-based pitch includes coal tar pitch and / or direct coal liquefaction pitch, and the petroleum-based heavy oil includes one or more of atmospheric and vacuum residue, catalytic slurry oil, ethylene tar, styrene tar, and other secondary processing tail oils. The catalytic slurry oil is a semi-solid or liquid substance produced during petroleum catalytic cracking and has a higher hydrogen content than coal-based pitch.
[0027] In one embodiment, the modifier disclosed herein is a compound such as a weak acid or a moderately strong acid, for example, it may include inorganic acids and / or organic acids, wherein the inorganic acid includes one or more of phosphoric acid, sulfuric acid, carbonic acid, and nitric acid, and the organic acid includes one or more of sulfonic acid, carboxylic acid, and amino acids. In a preferred embodiment, the modifier is phosphoric acid. In the above embodiments, by selecting the preferred modifier, it is beneficial to promote the crosslinking reaction between coal-based pitch and petroleum-based heavy oil to form a crosslinked product with a three-dimensional network structure.
[0028] In one embodiment of this disclosure, in step (1), the weight ratio of the coal-based pitch, petroleum-based heavy oil and modifier is 100:(10~50):(5~15).
[0029] In one embodiment, the crosslinking reaction is carried out at a temperature of 150-300°C, a heating rate of 1-10°C / min, and a holding time of 10-120min.
[0030] In one embodiment of this disclosure, in step (2), the curing temperature is 250~450℃, the constant temperature time is 1~8h, the heating rate is 1~5℃ / min, and the curing is carried out in an inert gas atmosphere; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen.
[0031] In one embodiment, the oxidation temperature is 250~450℃, the isothermal time is 1~5h, the heating rate is 1~5℃ / min, and the oxidation is carried out in an oxygen-containing gas atmosphere, which includes air or oxygen.
[0032] In one embodiment of this disclosure, the curing and oxidation are carried out continuously in a reactor. Preferably, the crosslinked asphalt is placed in the reactor for curing, and after curing is completed, oxygen-containing gas is introduced into the reactor to carry out the oxidation. In the above embodiment, the use of continuous curing and oxidation simplifies the method, makes the operating equipment simpler, the operation process easier to control, and the product performance more stable.
[0033] In one embodiment of this disclosure, the method further includes, before the curing in step (2), pulverizing the cross-linked asphalt using a pulverizer until the particle size D10 is <1μm, D50 is <5μm, and D90 is <10μm, to obtain cross-linked asphalt particles, and then subjecting the cross-linked asphalt particles to the curing process; the pulverizer includes an air jet mill or a ball mill, and may also be other types of pulverizers, without limitation. In the above embodiment, the preferred pulverizer is selected to facilitate the full progress of the subsequent reaction.
[0034] In one embodiment of this disclosure, the carbonization conditions in step (3) include: in an inert gas atmosphere, the oxidized asphalt is heated to 1100-1600°C at a heating rate of 1-10°C / min for carbonization, and the constant temperature time is 2-8h.
[0035] The second aspect of this disclosure provides a hard carbon material prepared using the method described in the first aspect of this disclosure.
[0036] This disclosure provides a sodium-ion battery in a third aspect, the sodium-ion battery comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode comprises the hard carbon material described in the second aspect of this disclosure.
[0037] The hard carbon material disclosed herein has the characteristics of high disorder and good sodium storage performance, and its application in sodium-ion batteries exhibits excellent electrochemical performance.
[0038] The present disclosure is further illustrated by the following examples, but the disclosure is not limited thereto. Unless otherwise specified, all raw materials used in the following examples are commercially available products. Coal tar pitch and petroleum-based heavy oil were produced in-house by the Research Institute of Petroleum Processing and Materials.
[0039] The morphological characteristics of hard carbon materials were analyzed using scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM), with Hitachi S4800 and JEM-2100 instruments respectively. The electrochemical performance of hard carbon materials was tested using a Blue Electricity testing system, instrument model CT3001A.
[0040] Example 1 (1) Coal tar pitch, deconsolidated oil slurry (catalytic oil slurry) and phosphoric acid (modifier) are mixed in a mass ratio of 100:30:10 and heated to 220℃ at a heating rate of 10℃ / min for crosslinking reaction. The temperature is held for 100min to obtain crosslinked pitch. The properties of coal tar pitch and deconsolidated oil slurry are shown in Table 1.
[0041] (2) The cross-linked asphalt was pulverized using an air jet mill until the particle size of D10 was <1μm, D50 was <5μm, and D90 was <10μm, thus obtaining cross-linked asphalt particles. The cross-linked asphalt particles were placed in a reactor to continuously complete curing and oxidation. The curing atmosphere was nitrogen, the temperature was 330℃, the holding time was 3h, and the heating rate was 3℃ / min. After curing, the temperature was maintained at 330℃, and the atmosphere was switched to air to start oxidation. The holding time was 3h, thus obtaining oxidized asphalt. (3) The oxidized asphalt was placed in a reactor under a nitrogen atmosphere for carbonization. The carbonization temperature was 1400℃, the constant temperature time was 2h, and the heating rate was 3℃ / min. Hard carbon material was obtained with a yield of 66%. The yield% = 100% × weight of hard carbon material in the product / (weight of coal tar pitch + desolidified oil slurry).
[0042] The SEM image of this hard carbon material is shown below. Figure 2 TEM image Figure 3 .
[0043] Figure 2 The hard carbon material prepared in Example 1 shows that it has a small particle size and a large specific surface area.
[0044] Figure 3 The hard carbon material prepared in Example 1 exhibits a graphite sheet structure characterized by short-range order and long-range disorder.
[0045] Example 2 Same as Example 1, except that the crosslinking temperature in step (1) is 230°C and the constant temperature time is 5 min.
[0046] Example 3 Same as in Example 1, except that: no pulverization is performed before curing in step (2), so that the cross-linked asphalt to be cured has a D10 particle size > 1 μm, a D50 particle size > 5 μm, and a D90 particle size > 10 μm.
[0047] Comparative Example 1 Same as in Example 1, except that the desolidified oil slurry in step (1) is replaced with the same amount of coal tar pitch.
[0048] Comparative Example 2 Same as in Example 1, except that the coal tar pitch in step (1) is replaced with the same amount of deconsolidated oil slurry.
[0049] Comparative Example 3 Similar to Example 1, except that in step (2), instead of curing, the cross-linked asphalt is directly oxidized.
[0050] Comparative Example 4 Same as Example 1, except that the deconsolidated slurry in step (1) is replaced with the same amount of petroleum-based asphalt, with an ash content of 0.03% and a hydrogen content of 5.4%.
[0051] Table 1 Properties of coal-based tar pitch and petroleum-based heavy oil
[0052] Note: "-" indicates that this item can be ignored.
[0053] Test case The hard carbon materials prepared in the examples and comparative examples were mixed with conductive carbon black and a binder to form a slurry, which was then uniformly coated onto aluminum foil and dried to form an electrode. A sodium metal sheet was used as the counter electrode, a glass fiber membrane was selected as the separator, 1 mol NaClO4 was used as the electrolyte, and DMC and EC (volume ratio 1:1) were used as the electrolyte solution to prepare a coin-type sodium-ion battery. The electrochemical performance of the sodium-ion battery was tested on an electrochemical workstation under the following conditions: constant current charge-discharge, constant temperature of 25°C, and charge-discharge voltage range of 0~2.8V. The test results are shown in Table 2. The charge-discharge curve of the battery assembled from the hard carbon material prepared in Example 1 at a current density of 0.1C is shown in Table 2. Figure 1 .
[0054] Table 2
[0055] As shown in Table 2, the hard carbon materials prepared using the method disclosed in Examples 1-3 exhibit high structural disorder and good sodium storage performance. When used in sodium-ion batteries, their reversible capacity can reach over 320 mAh / g, and they also possess a high initial discharge specific capacity. In contrast, Comparative Examples 1-4 did not employ the method disclosed in this invention, leading to the easy formation of large graphene sheets during carbonization, which is detrimental to the formation of hard carbon materials with high disorder. When the materials prepared in Comparative Examples 1-4 were used in sodium-ion batteries, the batteries exhibited lower reversible capacity and poorer electrochemical performance.
[0056] Depend on Figure 1 It can be seen that the sodium-ion battery assembled in Example 1 has a high charge and discharge capacity, indicating that the hard carbon material prepared in Example 1 has excellent electrochemical performance.
[0057] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0058] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0059] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A method for preparing hard carbon materials, characterized in that, The method includes: (1) Coal-based pitch and petroleum-based heavy oil are brought into contact with a modifier to undergo a crosslinking reaction, thereby obtaining crosslinked pitch; (2) The cross-linked asphalt is cured and oxidized to obtain oxidized asphalt; (3) Carbonize the oxidized asphalt.
2. The method according to claim 1, characterized in that, In step (1), the coal-based pitch has a hydrogen content of 7.0-9.0%, an oxygen content of 4.0% or more, an ash content of less than 0.01%, and a metal content of less than 10 μg / g; the petroleum-based heavy oil has a hydrogen content of 10.0-12.0%, an ash content of less than 0.01%, and a metal content of less than 50 μg / g.
3. The method according to claim 2, characterized in that, The coal-based pitch includes coal tar pitch and / or direct coal liquefaction pitch, and the petroleum-based heavy oil includes one or more of atmospheric and vacuum residue, catalytic slurry oil, ethylene tar, styrene tar, and other secondary processing tail oils. The modifier includes inorganic acids and / or organic acids, wherein the inorganic acids include one or more of phosphoric acid, sulfuric acid, carbonic acid and nitric acid, and the organic acids include one or more of sulfonic acid, carboxylic acid and amino acids.
4. The method according to claim 1, characterized in that, In step (1), the weight ratio of coal-based pitch, petroleum-based heavy oil and modifier is 100:(10~50):(5~15). The cross-linking reaction is carried out at a temperature of 150~300℃, a heating rate of 1~10℃ / min, and a holding time of 10~120min.
5. The method according to claim 1, characterized in that, In step (2), the curing temperature is 250~450℃, the constant temperature time is 1~8h, the heating rate is 1~5℃ / min, and the curing is carried out in an inert gas atmosphere; the inert gas includes one or more of nitrogen, helium, neon and argon, preferably nitrogen; The oxidation temperature is 250~450℃, the holding time is 1~5h, the heating rate is 1~5℃ / min, and the oxidation is carried out in an oxygen-containing gas atmosphere, which includes air or oxygen.
6. The method according to claim 1, characterized in that, The curing and oxidation are carried out continuously in a reactor. Preferably, the cross-linked asphalt is placed in the reactor for curing, and after the curing is completed, oxygen-containing gas is introduced into the reactor to carry out the oxidation.
7. The method according to claim 1, characterized in that, The method further includes, before the curing in step (2), using a pulverizer to pulverize the cross-linked asphalt until the particle size of D10 is <1μm, D50 is <5μm, and D90 is <10μm, to obtain cross-linked asphalt particles, and then allowing the cross-linked asphalt particles to undergo the curing; the pulverizer includes an air jet mill or a ball mill.
8. The method according to claim 1, characterized in that, In step (3), the carbonization conditions include: in an inert gas atmosphere, the oxidized asphalt is heated to 1100~1600℃ at a heating rate of 1~10℃ / min for carbonization, and the constant temperature time is 2~8h.
9. Hard carbon material prepared by the method according to any one of claims 1 to 8.
10. A sodium-ion battery, characterized in that, The sodium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator, wherein the negative electrode includes the hard carbon material as described in claim 9.
Citation Information
Patent Citations
Sodium-ion battery negative electrode material based on resin and asphalt as well as preparation method and application of sodium-ion battery negative electrode material
CN117902565A